Effects of supplemental feeding of Chinese herbal mixtures to perinatal sows on antioxidant capacity and gut microbiota of sows and their offspring piglets - Duan, Xuelei; Wang, Xiao; Li, Zhaonian; Liu, Chenggong; Bao, Yongzhan; Shi, Wanyu; Zhao, Xinghua (Frontiers in Microbiology, 2024)
A total of 60 healthy sows (Large white) at fourth parity were randomly assigned to five treatment groups. The control group received a basal diet, while the TRT1 group received a basal diet supplemented with 2 kg/t Bazhen powder (BZP). The TRT2, TRT3, and TRT4 groups were fed a basal diet supplementation with 1 kg/t, 2 kg/t, and 3 kg/t Qi-Zhu-Gui-Shao soothing liver and replenishing blood powder (QZGSP), respectively. The trial lasted for 5 weeks, starting from day 100 of gestation until day 21 of delivery. The results demonstrated that the inclusion of 2 kg/t and 3 kg/t QZGSP significantly enhanced the antioxidant capacity of sows and their offspring piglets to different degrees, thereby effectively alleviating oxidative stress. Analysis of gut microbiota revealed that QZGSP influenced the composition of gut microbiota in both sows and their offspring piglets. Specifically, at the genus level, the abundance of Christensenellaceae_R-7_group in the gut microbiota of sows in the TRT4 group was significantly lower than that in the TRT1 group (p < 0.05), while the relative abundance of Lactobacillus in the gut microbiota of sows in the TRT4 group was significantly higher than that in the CON group (p < 0.05). Furthermore, at the genus level, compared to those in the TRT1 group, piglets from the TRT4 group exhibited a significant decrease in relative abundance of Escherichia-Shigella, Parabacteroides, and Methanobrevivacter (p < 0.05), but a significant increase in Phascolarctobacterium (p < 0.05). Spearman correlation analysis indicated a positive correlation between relative abundance of Christensenellaceae_R-7_group and serum contents of T-AOC and CAT (p < 0.05), as well as a negative correlation with serum concentration MDA (p < 0.05). Additionally, there was a positive correlation between relative abundance Lactobacillus and serum levels SOD (p < 0.01) and GSH-Px (p < 0.05). Therefore, supplementation of 3 kg/t QZGSP in the periparturient sow diet significantly augmented antioxidant capacity in both sows and offspring piglets, while concurrently modulating the composition and structure of their intestinal microflora.